Mechanisms governing the enhanced strain tolerance of segmented APS-TBCs - Liuyu Yang; Yiwen Chen; Dingjun Li; Peng Jiang (Materials & Design)
Surface cracks are recognized as an effective approach for enhancing the strain tolerance of air plasma sprayed thermal barrier coating system (APS-TBCs). Therefore, segmented APS-TBCs with channeled surface cracks is considered a superior coating system for improving the combustion efficiency of advanced engines. However, the underlying mechanism responsible for its enhanced strain tolerance and service durability compared to conventional ones have not yet been fully elucidated. This article reveals this mechanism by investigating the residual stress evolutions in segmented and conventional APS-TBCs. We fabricate both types of APS-TBC samples and conduct isothermal cyclic oxidation service on them. Then, we measure the residual stresses of YSZ TC and TGO using Raman spectroscopy (RS) method and Photoluminescence piezo-spectroscopy (PLPS) method, respectively. Experimental results indicate that the segmented sample exhibited 2.5 times of service durability compared to the conventional sample. Through detailed analysis, we find that the macro-compliance mechanisms played a crucial role in governing the enhanced service performance of segmented samples. This macro-compliance effect is achieved by lowering the residual stress at given stain level through surface cracks, and thus results in improved interfacial integrity compared to conventional ones. The discoveries in this study contribute towards comprehending microstructure design and selection of APS-TBCs.